E-Government Development on Control Corruption: A Lesson Learned from Singapore - Sukarno, Mohamad; Rodriguez, Mike Joy; Nursamsiyah, Nursamsiyah (Journal of Governance and Public Policy, 2024)
This study explores the success of e-government in controlling corruption in Singapore and its potential applicability in Indonesia. Using a qualitative approach and literature review, it assesses anti-corruption efforts based on the E-Government Development Index (EGDI), focusing on the Online Service Index (OSI), Telecommunication Infrastructure Index (TII), and Human Capital Index (HCI). The findings reveal that Singapore, through its Corrupt Practices Investigation Bureau (CPIB), has effectively used digital platforms like e-complaints, e-booking systems, and AI-driven solutions to strengthen anti-corruption efforts. In contrast, Indonesia faces challenges due to a lower EGDI, particularly in underdeveloped TII, and a need for stronger AI support and legal reforms. The Corruption Eradication Commission (KPK) also requires improvements in human resources, with a shift towards meritocracy to reduce conflicts of interest. Unlike Singapore’s independent anti-corruption framework, Indonesia's KPK is constrained by administrative processes and supervisory involvement, limiting its capacity to combat corruption effectively. The current research builds upon existing studies by integrating the EGDI indicators with a focus on e-government’s role in corruption control, a dimension that has been underexplored, especially in comparative analyses between Singapore and Indonesia. The use of digital platforms in anti-corruption efforts and AI integration, as seen in Singapore, represents an advanced approach in this field. The novelty of this research lies in its detailed examination of the technological and institutional gaps between Singapore and Indonesia in implementing e-government for corruption control.